What shapes traditional food plant use? Correlates of consumption and associations with perceived well-being in three socio-ecological settings of Indonesia - Rahayu, Yenyen Sally; Suwardi, Adi Bejo; Anggraeni, Anisa; Irsyam, Arifin Surya Dwipa; Purwaningtias, Raissa Manika; Sujarwo, Wawan (Ethnobotany Research and Applications, 2025)
Background: Traditional food plants (TFPs) are integral to dietary resilience in Indonesia, yet their consumption dynamics and potential health links remain understudied. This study aims to document TFPs’ use, examine factors correlated with consumption, and explore their associations with perceived health and well-being. Methods: A cross-sectional survey of 335 participants in three socio-ecologically distinct provinces (West Java, West Nusa Tenggara, Aceh) employed food frequency questionnaires and a standardized self-rated health and well-being survey. Bivariate correlation and multiple regression analyses were applied to analyze the associations. Results: We documented 121 TFP species from 49 families. Frequent consumption was most common in West Nusa Tenggara (61%), followed by Aceh (42%) and West Java (15%), with most TFPs sourced from unmanaged landscapes. Agricultural and dietary factors were the most consistent correlates of TFP consumption across sites. Associations with well-being varied by location. In West Java, TFP intake was associated with a mental well-being component (Social Functioning). In West Nusa Tenggara, it was associated with a mental component (Mental Health) and a physical component (General Health). In Aceh, an initial association with a physical component (General Health) was not significant after adjusting for confounders. Conclusions: The relevance of TFPs persists across Indonesia’s diverse socio-ecological settings. As consumption patterns and perceived benefits of well-being are context-specific, promotion efforts could be locally tailored and coupled with efforts to protect access to natural habitats. Keywords: Traditional food plants, Well-being, Consumption pattern, Indonesia, Ethnobotany